TREATMENT RESULTS OF CONCURRENT CHEMORADIOTHERAPY WITH THE FOLFOX REGIMEN FOR STAGE II-IVA ESOPHAGEAL CANCER AT NGHE AN ONCOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the clinicopathological characteristics and treatment outcomes of concurrent chemoradiotherapy with the FOLFOX regimen in patients with stage II-IVA esophageal cancer.Methods: A retrospective descriptive study was conducted on 45 patients with stage II-IVA esophageal cancer who received concurrent chemoradiotherapy using the FOLFOX regimen at Nghe An Oncology Hospital between January 2023 and September 2025.Results: The mean age of the patients was 63.5 ± 6.5 years, and 95.6% of patients were male. Squamous cell carcinoma accounted for 93.3% of cases, with tumors most commonly located in the middle third of the esophagus (48.9%). Most patients presented with stage III-IVA disease (91.1%), T3-T4 tumors (86.7%), and ECOG performance status 0-1 (93.4%). After concurrent chemoradiotherapy, the objective response rate and disease control rate were 77.8% and 91.1%, respectively. Following adjuvant chemotherapy, objective response rate was 73.3%, disease control rate increased to 93.3%, and the complete response rate improved from 11.1% to 26.7%. The median PFS was 10.0 ± 2.1 months (95% CI: 5.8-14.2 months). The 6-month, 12-month, and 18-month PFS rates were 72.8%, 46.7%, and 30.3%, respectively. Treatment-related toxicities were generally mild to moderate. Grade 3 neutropenia and grade 3 radiation esophagitis occurred in 4.4% and 6.7% of patients, respectively. No grade 4 toxicities or renal toxicity were observed.Conclusions: Concurrent chemoradiotherapy with the FOLFOX regimen demonstrated favorable efficacy, with high response and disease control rates, acceptable progression-free survival, and manageable toxicity in patients with stage II-IVA esophageal cancer. These findings support FOLFOX-based concurrent chemoradiotherapy as an effective and well-tolerated treatment option in routine clinical practice.
Keywords: Esophageal cancer, concurrent chemoradiotherapy, FOLFOX.